Penerapan Pola Asuh Orang Tua dan Kesehatan Mental - Ana Meysari (UNIVERSITAS SERAMBI MEKKAH, 2024)
Parenting is a responsibility as a parent towards the child. Parenting is a pattern of caring for parents towards children, namely how parents treat children, educate, guide and discipline and protect children in the process of reaching maturity and shaping children's behavior accordingly. with good norms and values ​​and in accordance with community life. If parents use appropriate parenting styles, children will have good mental health. This research is included in the type of descriptive research with a qualitative approach. The data collection technique in this research uses observation techniques, interviews. This observation technique is carried out by observing research subjects, family environment and so on. The interview technique is carried out spontaneously (unstructured) with the research subject regarding the research object, namely by asking questions and answers with the research subject. Parental awareness in providing the best parenting style for children must be instilled in each individual as a parent. So, by implementing appropriate parenting patterns, children's mental health will be good and maintained. And have a peaceful, comfortable and happy family life. Because a person's mental health is very valuable.